Macroeconomic and Institutional Determinants of Capital Structure Decisions - Marco Botta; Luca Colombo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2016)
We investigate the capital structure of a large sample of corporations in 52 countries, focusing on the effects of macroeconomic and institutional characteristics on firms' dynamic behavior. We find that these characteristics affect both the optimal level of leverage and the adjustment process towards it. The speed of adjustment varies significantly with both macroeconomic and institutional conditions for financially unconstrained firms, while it is unaffected for constrained firms. Overall, our results support a complex view of capital structure decisions, where market timing and pecking order arguments affect the short-run, while dynamic trade-off with costly readjustment matters in the long-run.
Keywords: C23; E44; G32; 330; Capital Structure Dynamics; Debt Readjustments; Dynamic Adjustment Models; Macroeconomic Conditions; Speed of Adjustment